Symbiotic Binary YY Her Eclipses, Flares and Outbursts - Hric, L.; Gális, R.; Niarchos, P.; Gazeas, K. (2006)
The long-term CCD and photoelectric observations of YY Her covering the period of its post-outburst activity (JD 2 451 823 -- 2 452 996) are presented. We explain the periodic variations of the brightness of YY Her by the eclipses of the components in the system. The model with a deformed (non-homogeneous) envelope, surrounding the white dwarf is discussed. In addition, we observed a flare in about JD 2 452 440, during the primary minimum, that was later followed by an energetic outburst in JD 2 452 700.
Keywords: Stars: Binaries: Symbiotic; Stars: Individual: YY Her